Atividade gastroprotetora e antimicrobiana do extrato seco de matricaria recutita (Camomila) e do Alfa-Bisabolol : possíveis mecanismos de ação - Bezerra, Suzana Barbosa (2009)
Matricaria recutita, commonly known as chamomile, is a plant species used in medicine due to its sedative properties, anti-inflammatory and healing, among others. Alpha-bisabolol, a sesquiterpene present in essential oil, also has several pharmacological activities recognized. This work evaluated the gastroprotective activity, antioxidant, antimicrobial and cytotoxic activities from chamomile dried flowers extract (CDFE) and alpha-bisabolol (BISA). Gastroprotective activity for ESFC at doses 100, 200 and 400 mg / kg, orally, significantly reduced in 78, 68 and 89% respectively (p <0.001) gastric lesions induced by ethanol (1.0 mL / animal). BISA also inhibited the formation of ulcers induced by ethanol, but only at doses 50 and 100 mg / kg (87% and 96%, respectively). The mechanism of gastroprotective the BISA in gastric lesions induced by ethanol in rats was evaluated at a dose of 100 mg / kg. The pre-treatment with the antagonist of nitric oxide (L-NAME) or antagonist of prostaglandins (indomethacin) did not blocked effectively of BISA, but the pretreatment with glibenclamide, an inhibitor of K+ATP channels, reduced significantly (p <0.05) the gastroprotective effect of BISA. These results indicate that BISA can reduce the damage of gastric mucosa induced by ethanol through the mechanism of activation of K+ATP channels. To evaluate the antioxidant potential measured by the DPPH test, both as ESFC and BISA showed no scavenging activity of free radicals. The method of agar diffusion was used to determine the antimicrobial potential of ESFC and BISA on microbial strains originating from ATCC and hospital origin. The ESFC was not able to inhibit the growth of any of the bacterial strains tested and required only a small inhibition for the yeast C. albicans at a concentration of 5 mg / mL. BISA inhibited the growth of S. aureus ATCC 6538, C. albicans ATCC 10231, Klebsiella pneumoniae and Acinetobacter balmanii at concentrations of 0,0625, 0.0625, 4 and 4 mg / mL, respectively. The highest antimicrobial activity of BISA was demonstrated against Gram-positive S. aureus ATCC 6538, with an MIC of 1mg/mL and MLC greater than 1mg/mL. For the other strains tested, the MIC and the CLM ESFC and BISA were greater than 1mg per mL. From the results obtained was performed to evaluate the cytotoxicity of ESFC and BISA. Human neutrophils were isolated and were ESFC and BISA (1,5,10,50 and 100 mg / mL), where ESFC proved cytotoxic at all doses tested, while the BISA not only showed cytotoxic activity at dose of 5 mg / mL. The results of this study suggest that ESFC and BISA have gastroprotective activity in gastric lesions induced by ethanol, where the mechanism of action of BISA seems to be related to activation of K+ATP channels. However, it was not possible to determine the antioxidant activity of two drugs test by the DPPH test. The best result for the antimicrobial activity of BISA was demonstrated for the bacteria S. aureus ATCC 6538, with MIC 1mg/mL also being demonstrated cytotoxic activity for that substance.